Effect of Garlic (Allium sativum) and Tulsi (Ocimum sanctum) Leaf Powder Supplementation on Growth Performance and Carcass Traits in Broiler Chicken - Kumar, Rakesh; Maan, N.S.; Sihag, Sajjan; Sheoran, Nancy; Baloda, Saurabh; ., Promila; Shunthwal, Jyoti (Indian Journal of Animal Nutrition, 2018)
The experiment was designed to evaluate the effect of supplementing different levels of garlic and tulsi (Ocimum sanctum) leaf powder in diet on growth performance and carcass yields in broiler chicken. A total of 280 day-old commercial broiler chicks (Vencobb-400) were randomly distributed into seven treatments, each treatment had four replicates with ten chicks in each replicate. The control group T1 was fed a basal diet formulated as per BIS (2007) while in treatment groups T2 and T3 basal diet was supplemented with garlic powder @ 0.5 and 1%; T4 and T5 were supplemented with tulsi leaf powder @ 0.5 and 1%; and chicks of T6 and T7 were fed diets supplemented with combinations of garlic powder and tulsi leaf powder @ 0.5 and 1.0% of each, respectively. The body weight gain was (P